Studi Tentang Proses Produksi Tahu pada Industri Rumah Tangga di Dusun Jambu Lor - Khasan Azabit; Rachmat Fauzi; Hanum Nur Sulistiyawati; Faiz Zulfikar; Mudhoffar, Mudhoffar; Maitsa Khoirunnida Nurrohman; Alfiani Fathur Rizqi; Robby Dzulkarnain (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the tofu production process in the household industry in Jambu Lor Hamlet. This research was conducted using observation methods and in-depth interviews with household tofu entrepreneurs in the area. The main focus of this study is to describe the stages of tofu production, starting from the selection of raw materials, the manufacturing process, to the distribution stage of the finished product. In addition, this study also evaluated factors that affect the quality of tofu products, such as soybean selection, processing techniques, and the influence of the surrounding environment. The results showed that despite using simple equipment, the household industry in Jambu Lor Hamlet was able to produce tofu with good quality, with some innovations in the production process tailored to the needs of the local market. This study is expected to provide useful insights for the development of the household tofu industry in the region and strengthen the local economic sector.